Beamed and Unbeamed Emission of γ-Ray Blazars. (6th October 2020) - Pei, Zhiyuan; Fan, Junhui; Yang, Jianghe; Bastieri, Denis
Abstract: A two-component model of radio emission has been used to explain some radio observational properties of Active Galactic Nuclei (AGNs) and, in particular, of blazars. In this work, we extend the two-component idea to the γ -ray emission and assume that the total γ -ray output of blazars consists of relativistically beamed and unbeamed components. The basic idea leverages the correlation between the radio core-dominance parameter and the γ -ray beaming factor. To do so, we evaluate this correlation for a large sample of 584 blazars taken from the fourth source catalog of the Fermi Large Area Telescope (Fermi-LAT) and correlated their γ -ray core-dominance parameters with radio core-dominance parameters. The γ -ray beaming factor is then used to estimate the beamed and unbeamed components. Our analysis confirms that the γ -ray emission in blazars is mainly from the beamed component.